Pengaruh likuiditas, kualitas aktiva, sensitivitas pasar, efisiensi, dan profitabilitas terhadap CAR pada bank devisa yang go public - Hadi Susilo Dwi Cahyono; Anggraeni Anggraeni (STIE Perbanas Surabaya, 2015)
CAR is one indicator used to measure the bank capital adequacy. Capital for bank is used to absorb loss emerged from banking activities, and as the basis of some policies releasead by Indonesia Bank. This research tries to investigate whether the independent variables of LDR, IPR, APB, NPL, IRR, PDN, BOPO, FBIR, ROA, and ROE both simultaneous-ly and partially have significant effect on CAR and which variable has the dominant effect on CAR. This research uses secondary data taken from financial statements from period I Quarterly of 2010 until II Quartely in 2014 of the go-public national private banks. The sample consists of PT. Internasional Indonesia Bank, Tbk, PT. Permata Bank, Tbk, and PT. Pan Indonesia Bank, Tbk. The data were processed by using SPSS 11.5 input results and F-test to see the effect simultaneously as well as t-test to see the effect partially. It shows that LDR, IPR, APB, NPL, IRR, PDN, BOPO, FBIR, ROA, and ROE simultaneously have significant effect on CAR. Yet, partially, only IPR, APB, and PDN have significant effect on CAR. The most dominant is APB that is 23.45 percent.